Tick-borne encephalitis virus subtypes: mono- and mixed infection in specific and non-specific ticks - Polienko, Alexandra E.; Belova, Oxana A.; Litov, Alexander G.; Rogova, Anastasia A.; Karganova, Galina G. (Frontiers in Cellular and Infection Microbiology, 2025)
Tick-borne encephalitis virus (TBEV) is traditionally divided into three main subtypes – European (Eu), Siberian (Sib) and Far Eastern (FE), the distribution of which is confined to the areas of the main vectors, Ixodes ricinus (TBEV-Eu) and Ixodes persulcatus (TBEV-Sib, TBEV-FE). Dermacentor reticulatus also can act as competent vector and participate in TBEV circulation together with the main vectors. It is suggested that there is a specific adaptation not only between TBEV variant and certain tick species, but also between virus variant and local populations of one tick species. In our study, we percoxally infected two populations of I. ricinus, I. persulcatus and D. reticulatus collected in remote areas with three TBEV strains of the main subtypes. Dynamics of the number of TBEV RNA copies and of the number of infectious for mammalian cells virus particles during mono- and mixed infection of ticks were estimated by real-time PCR and plaque assay in PEK cell culture, respectively. Data was obtained that I. ricinus, I. persulcatus and D. reticulatus effectively support the reproduction of TBEV regardless of the strain. Interpopulation differences of local populations of one tick species in the maintenance of TBEV reproduction were revealed in I. persulcatus during mono- and mixed infection and in I. ricinus during mixed infection. Despite minor differences in the level of virus reproduction in ticks, we observed changes in the infectivity of TBEV strains for mammalian cell culture during persistence in different species of ticks. Notably, the TBEV-Eu increased infectivity during adaptation to a non-specific tick species. Thus, we demonstrated that the level of virus reproduction is not the primary factor that determines the adaptation of TBEV to a new tick species. The nature of changes in TBEV infectivity depends on the virus strain and the species of ticks.